Outcomes of cPRA 100% deceased donor kidney transplant recipients under the new Kidney Allocation System: A single‐center cohort study. Issue 10 (22nd May 2020) - Jackson, Kyle R.; Chen, Jennifer; Kraus, Edward; Desai, Niraj; Segev, Dorry L.; Alachkar, Nada
Abstract : In light of changes in donor/recipient case‐mix and increased cold ischemia times under the Kidney Allocation System (KAS), there is some concern that cPRA 100% recipients might be doing poorly under KAS. We used granular, single‐center data on 109 cPRA 100% deceased donor kidney transplant (DDKT) recipients to study post‐KAS posttransplant outcomes not readily available in national registry data. We found that 3‐year patient (96.4%) and death‐censored graft survival (96.8%) was excellent. We also found that cPRA 100% recipients had a relatively low incidence of T cell–mediated rejection (9.2%) and antibody‐mediated rejection (AMR) (13.8%). T cell–mediated rejection episodes tended to be relatively mild—50% (5 episodes) were grade 1, 50% (5 episodes) were grade 2, and none were grade 3. Only 1 episode was associated with graft loss, but this was in the context of a mixed rejection. Although only 15 recipients (13.8%) developed an AMR episode, 2 of these were associated with a graft loss. Despite the rejection episodes, the vast majority of recipients had excellent graft function 3 years posttransplant (median serum creatinine 1.5 mg/dL). In conclusion, cPRA 100% DDKT recipients are doing well under KAS, although every effort should be made to prevent AMR to ensure long‐term outcomes remain excellent. Abstract : In this single‐center study of cPRA 100% kidney transplant recipients under the Kidney Allocation System, the authors report excellent patient survival, death‐censored graft survival and graft function at 3 years, and a low incidence of T cell– and antibody‐mediated rejection.